Dampak Program Keluarga Harapan dalam Pengentasan Kemiskinan di Desa Bangga Kecamatan Paguyaman Pantai - Latare, Sainudin; Harold, Rudy; Bumulo, Sahrain; Ali, Ahmad (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2023)
The Family Hope Program (PKH) is a social assistance program that is provided to help poor families in rural areas. According to the Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 1 of 2018 concerning the Family Hope Program, it is explained that